Long-term follow-up after separate replacement of the aortic valve and ascending aorta - Karck, Matthias; Laas, Joachim; Heinemann, Markus K.; Borst, Hans Georg (Herz, 1992)
Between May 1974 and November 1991, 28 patients underwent a separate replacement of the aortic valve and the ascending aorta (20 male, eight female; 32 to 71 years old, x = 52 years). 23 patients were operated for ascending aortic aneurysm, three for chronic and two for acute aortic dissection type A. 17/18 patients living at the beginning of this study were re-investigated after a mean follow-up interval of 8.5 years postoperatively with DSA, thoraco-abdominal CT and echocardiography. 1/8 biological aortic valves and 1/20 mechanical valves had to be replaced (four years and two months postoperatively) for valve degeneration and paravalvular leakage respectively. Three patients developed a sinus of Valsalva aneurysm and were reoperated five, 9.2 and 9.3 years after primary repair. In all three patients histological signs of idiopathic degenerative media disease of the aorta were found. Two other patients presented with a perfused perigraft channel and therefore had to be reoperated. Patients with chronic aortic dissection type A and/or ascending aortic aneurysms presenting clinical or intraoperative signs of degenerative media disease of the aorta should undergo composite graft replacement to preclude formation of sinus Valsalva aneurysms.
Gesehen am 12.01.2022